Uncovering the Human and Divine Aspect of Ridha in the Qur’an through the Lens of Tafsir Tahrir wa Tanwir - Yudha, Muhammad Aga (Jurnal Studi Ilmu-ilmu Al-Qur’an dan Hadis, 2023)
This article explores the concept of Ridha in the Qur’an, focusing on its background and purpose. The concept of Ridha is inseparable from the ongoing debate between Sunnis and Shiites, who have differing interpretations of the concept in order to legitimize their respective ideologies. The study employs a thematic method, analysing the views of Ibn Asyur in the tafsir Tahrir wa Tanwir, which relates to the concept of Ridha. The results reveal that Ibn Asyur divided the concept into two: Ridha among fellow humans and Ridha from God to His creations. The Qur’an, being a holy text that guides mankind, delves into the topic of Ridha and presents it in two aspects: Ridha Allah and Ridha man. Although these two aspects appear together in the same verse, the Qur’an also emphasizes the inequality of God with His being (tanzih), making both types of Ridha part of the mutasyabihat concept. To fully understand the meaning, it is necessary to differentiate between Ridha Allah and Ridha Human. Through his book, Tahrir wa Tanwir, Ibn Asyur aims to provide a comprehensive understanding of Ridha from both the human aspect and as the nature of Allah SWT.